Optimasi Jenis dan Konsentrasi Zat Pengatur Tumbuh Serta Pencahayaan untuk Pertumbuhan Plantlet Phalaenopsis sp. Secara In Vitro - Wakidah, Koriatun; Rahayu, Enni Suwarsi (Universitas Negeri Semarang, 2020)
Moon orchid is on of many oriental plant that have high economic value. Orchid seeds are difficult to germinate in the conventional way. Germination can be through plant tissue culture. Orchid growth produced by tissue cultures is enhanced by plant hormones and light intensity. The purpose of the reserch was to analyze the effects of the concentration of Napthalene acetic acid (NAA), Benzyl Amino Purin (BAP) and light intensity of the growth of the Phalaenopsis sp. This research was carried out using group randomized factorial design with three factors: light intensity (3400 lux, 4400 lux dan 5400 lux), NAA concentration (0.5 ppm; 1 ppm; 1.5 ppm) and BAP concentration (1 ppm; 1.5 ppm; 2 ppm) in Vacin and Went (VW) media and each bottle contained 5 plantlets and repeated as many as 2 repetitions. The parameters observed were the number of leaves, length, leaf width, number of roots, root length and level of chlorophyll of the leaf. Data were analyzed with three-way Anova and Duncan's Multiple Range Test. The results showed that The conentration of NAA hormone has significant effects on total chlorophyll levels. The conentration of BAP hormone does not significantly affect the growth of the plantlet. The light intensity was significant to the leaf width and the chlorophyll content. The interaction of 0.5 ppm NAA, 2 ppm BAP and light intensity 4400 lux produced the largest leaf. NAA 0,5 ppm was optimum to the chlorophyll content. The light intensity at 4400 lux was significant to the leaf width and the chlorophyll content. Anggrek bulan adalah salah satu tanaman hias yang memiliki nilai ekonomi tinggi. Biji anggrek sulit berkecambah dengan cara konvensional. Perkecambahan dapat dilakukan melalui kultur jaringan tanaman. Pertumbuhan anggrek hasil kultur jaringan tanaman ini dipengaruhi oleh hormon pertumbuhan dan intensitas cahaya. Penelitian ini bertujuan untuk menganalisis pengaruh konsentrasi Napthalene acetic acid (NAA), Benzyl Amino Purin (BAP) dan intensitas cahaya terhadap pertumbuhan anggrek Phalaenopsis sp. Penelitian ini menggunakan rancangan acak kelompok tiga faktor yaitu intensitas cahaya (3400 lux, 4400 lux dan 5400 lux), konsentrasi NAA (0,5 ppm; 1 ppm; 1,5 ppm) dan konsentrasi BAP (1 ppm; 1,5 ppm; 2 ppm) dalam media Vacin and Went (VW) dan setiap botol berisi 5 plantlet dan diulang sebanyak 2 ulangan. Parameter yang diamati adalah jumlah daun, panjang daun, lebar daun, jumlah akar, panjang akar, dan kadar klorofil total daun. Data dianalisis dengan Anava tiga jalur dan Duncan’s Multiple Range Test. Hasil penelitian menunjukkan bahwa konsentrasi hormon NAA berpengaruh signifikan terhadap kadar klorofil total, hormon BAP tidak berpengaruh signifikan terhadap pertumbuhan, intensitas cahaya berpengaruh signifikan terhadap pertumbuhan lebar daun dan kadar klorofil total. Interaksi 0,5 ppm NAA, 2 ppm BAP pada intensitas cahaya 4400 lux berpengaruh signifikan terhadap pertumbuhan lebar daun. Hormon NAA 0,5 ppm optimal terhadap kadar klorofil total, intensitas cahaya 4400 lux optimal terhadap pertumbuhan lebar daun, dan kadar klorofil total anggrek bulan